Purification, biochemical characterization and antimicrobial activity of a novel 2s albumin from castor bean(ricinus cmmunis L.) cake displaying trypsin inhibitory activity - Pedro Filho Noronha de Souza (2012)
Castor bean (Ricinus communis L.) is an important crop for the Northeast of Brazil, which recently has been used to produce biodiesel. Around 90% of the castor bean production in Brazil is concentrated at Northeast region and the state of CearÃ is the second largest producer. During the oil extraction process from the castor bean seeds, a resulting residue, called castor cake, is underutilized. However, this byproduct is rich in protein and micronutrients such as nitrogen, phosphorus and potassium, an attribute that qualifies it as a stuff that could be used as organic fertilizer or as animal feed, for example, bringing added value to it. Unfortunately, its use as food has not been possible because of the presence of toxic elements and allergens (ricin, ricinine, complex allergens) in its composition, unless it were previously submitted to a detoxification process. To date, the existing technologies to this end are not economically viable on an industrial scale. Therefore, studies to add value to this abundant byproduct generated in the castor bean biodiesel productive chain is of paramount importance. Thus, in this context, this study was performed to identify, isolate, purify and characterize new bioactive molecules of de-oiled castor cake with biotechnological potential. Through extraction of soluble proteins with 50 mM Tris-HCl pH 7.5, fractionation with ammonium sulfate (50-75%), following by hydrophobic interaction chromatography in Phenyl-Sepharose column and ion exchange chromatography (DEAE-Sepharose), a protein, named Rc-2S-Alb, able to inhibit trypsin was purified. Rc-2S-Alb has a molecular mass of approximately 75.8 kDa, as determined by SDS-PAGE, and under reducing conditions showed a large and a small protein band of 15.8 kDa and 10.5 kDa, respectively. Its NH2-terminal sequence showed similarity with the following proteins: putative 2S albumin precursor (89%), chain A of RicC3 (89%), and chain A of mabilin-1 (89%), all from R. communis seeds; and with the short chain of a "napin-like" protein from Brassica napus (89%). In addition, these similar proteins have two highly conserved domains: QEVQRKDLS and YLRQS. Comparison of the partial primary structure of Rc-2S-Alb generated by the ESI-Q-TOF MS/MS analysis of 17 tryptic peptides, showed 43% similarity to Mabinlin-1 (pI/Mr 6.7 and 29.3 kDa) from R. communis. There were also high similarities among the three-dimensional structures of Rc-2S-Alb, RicC3 and Mabinlin-1. Rc-2S-Alb did not inhibit the spore germination of the phytopathogenic fungi Fusarium oxysporum and Rizoctonia solani, but promoted aggregation of their respective spores. Moreover, Rc-2S-Alb did not inhibit the mycelial growth of Fusarium oxysporum, Fusarium solani, Rizoctonia solani and Collethotricum gloeosporioides. Contrary, Rc-2S-Alb was effective in inhibiting the growth of the human pathogenic bacteria Pseudomonas aeruginosae, Klebsiella pneumoniae and Bacillus subtilis, at low concentrations. In conclusion, it was established a protocol to purify a new 2S albumin from castor bean cake, which inhibits trypsin and has important antibacterial activity. Thus, the Rc-2S-Alb should be further studied in order to verify its effectiveness as new alternative therapeutic agent against resistant bacteria to commercial antibiotics, which will contribute to improve the human health.